Minimally invasive liver resection for hepatocellular carcinoma of patients with liver damage B: A propensity score‐based analysis. Issue 7 (7th March 2018) - Noda, Takehiro; Eguchi, Hidetoshi; Iwagami, Yoshifumi; Yamada, Daisaku; Asaoka, Tadafumi; Gotoh, Kunihito; Kawamoto, Koichi; Kobayashi, Shogo; Hashimoto, Yasuji; Takeda, Yutaka; Tanemura, Masahiro; Umeshita, Koji; et al.
Abstract : Aim: Minimally invasive liver resection (MILR) is considered a safe and feasible treatment for malignant liver tumors. However, few studies have investigated the surgical outcomes of MILR in patients with impaired liver function. Liver damage is used for consideration of hepatectomy. The aim of this study is to clarify the efficacy of MILR for patients with impaired liver function by using propensity score matching. Methods: Ninety‐nine patients with liver damage B underwent hepatic resection were analyzed. The patients were divided into two groups, the MILR group ( n  = 24) and the open liver resection (OLR) group ( n  = 75). After matching of a propensity score, we compared clinicopathological features and surgical outcomes. Results: After matching, 36 patients (18 patients from each group) were selected and the patients' characteristics and tumor characteristics were not significantly different between the two groups. Blood loss ( P  = 0.0163) and complication rate ( P  = 0.0162) were significantly decreased in the MILR group. Complications were observed in eight patients, comprising one patient in the MILR group and seven patients in the OLR group. The postoperative hospital stay was significantly shortened in the MILR group ( P  = 0.0118). Conclusion: Minimally invasive liver resection might be effective for patients with impaired liver function. It reduces surgical complications and consequently shortens hospitalization time.